A NOVEL TECHNIQUE TO DETECT THE MISBEHAVING NODES IN DELAY TOLERANT NETWORKS - Begum M, Ms Yasmeen; Bala, Smt. M Sri (IJRDO -Journal of Computer Science Engineering, 2015)
Delay Tolerant Network(DTNs) are a class of different network characterized like lack of guaranteed relatedness ,typically low frequency between DTN bud and long propagation delay within the networks. Existing beat algorithms for DTN assumes that nodes are active to forward packets for others but in real word selfish and malevolent behaviors occurs while forward packets for nodes. Due to different characteristics the message propagation action DTNs follows a Store-Carry and Forward amenities. In this paper, we propose iTrust, probabilistic misbehavior disclosure schemes for secure and to advance the efficiency of DTN routing towards able trust establishment. The elemental idea of iTrust is introducing Trusted Authority (TA) to judge the nodes action based on the collected routing clue and probabilistically checking. To further advance the performance of the proposed probabilistic inspection blueprint, we introduce a reputation system. The extensive inquiry and simulations result shows that the proposed blueprint substantiate the effectiveness and ability of the proposed schemes.